(untitled) (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2024)
In the article on the educational program “Physics and Mathematics Education”, a program of adaptive psychological and pedagogical practice planned in this undergraduate educational program has been developed. The learning outcomes of adaptive psychological and pedagogical practice were structured in such a way that they would ensure the achievement of the goals and learning outcomes of the educational program. The stages, content, types of work, the allotted time for their implementation and forms of ongoing monitoring of practice have been developed.